2017
DOI: 10.5858/arpa.2016-0269-oa
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Diagnostic Yield Achieved With On-site Pathology Evaluation of Fine-Needle Aspiration–Assisted Core Biopsies for Pediatric Osseous Lesions: A Single-Center Experience

Abstract: Context.-Image-guided, fine-needle aspiration-assisted core needle biopsy with an on-site evaluation by a pathologist (FNACBP) of osseous lesions is not a common practice in pediatric institutions.Objectives.-To evaluate the diagnostic adequacy and accuracy of FNACBP for pediatric osseous lesions and to compare the adequacy with procedures that do not use fine-needle aspiration.Design.-Six-year, retrospective review of 144 consecutive children biopsied for osseous lesions with and without fine-needle aspiratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…A multidisciplinary team approach is paramount to ensure adequate tumor specimens for PDX generation of bone sarcomas in pediatric patients without compromising diagnostic accuracy. Our 6 year experience with percutaneous core biopsies of pediatric osseous lesions reported 100% specificity, sensitivity, and positive predictive value in accurate diagnosis of all the malignant lesions biopsied . On‐site evaluation of tumor biopsies by cytopathologists has become the standard practice at our institution for patients with suspected bone sarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…A multidisciplinary team approach is paramount to ensure adequate tumor specimens for PDX generation of bone sarcomas in pediatric patients without compromising diagnostic accuracy. Our 6 year experience with percutaneous core biopsies of pediatric osseous lesions reported 100% specificity, sensitivity, and positive predictive value in accurate diagnosis of all the malignant lesions biopsied . On‐site evaluation of tumor biopsies by cytopathologists has become the standard practice at our institution for patients with suspected bone sarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…The literature on the pediatric population is sparse. Patel et al showed an increase in the diagnostic rate of pediatric CNB in bone lesions from 79% to 97% when on‐site FNA and cytology were added 12 . Our results for a variety of tumors in the pediatric population were very promising, yet the cohort was small.…”
Section: Discussionmentioning
confidence: 61%
“…The role of cytopathology has evolved over the years from a purely diagnostic technique to an adjuvant method that guides decisions for other sampling procedures 10‐13 . On‐site cytology followed by CNB in the adult population improves diagnostic success compared to CNB alone, and it is becoming generally accepted that the two procedures together are synergistic 10‐14 . Additionally, the cytological technique was first used with FNA only and has evolved to include TI from core biopsies 15 …”
Section: Discussionmentioning
confidence: 99%
“…The overall diagnostic FNAB yield was 98.0%, with a 72.0% diagnostic accuracy for a specific lesion diagnosis (overall diagnostic accuracy 95.3%) which is comparable to similar other studies. 14 , 15 , 16 , 17 , 18 A treatment plan could be initiated in most cases based on a specific diagnosis confirmed via FNAB.…”
Section: Discussionmentioning
confidence: 99%